2017
DOI: 10.1097/pec.0000000000000863
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Emergency Department Observation Units for Neurologically Intact Children With Head CT Abnormalities Secondary to Acute Closed Head Injury

Abstract: Neurologically intact patients on initial ED evaluation had a very low likelihood of requiring further interventions, irrespective of CT findings. Although prospective evidence is necessary, this supports reliance on clinical findings when evaluating a well-appearing child with an acute CHI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
1
0
4
Order By: Relevance
“…These findings are consistent with prior studies that emphasize that the pathology revealed on head CT must be interpreted within the clinical picture of the patient when determining the duration or level of hospitalization. 3,23,44 Certain constellations of imaging features, GCS scores, and neurological statuses had a particularly strong relationship with potentially unavoidable transfers. We noted that 29 patients were transferred with negative imaging and a GCS score of 15, with no reported seizures or loss of consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with prior studies that emphasize that the pathology revealed on head CT must be interpreted within the clinical picture of the patient when determining the duration or level of hospitalization. 3,23,44 Certain constellations of imaging features, GCS scores, and neurological statuses had a particularly strong relationship with potentially unavoidable transfers. We noted that 29 patients were transferred with negative imaging and a GCS score of 15, with no reported seizures or loss of consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…소아청소년과 전공의 수련이 단층촬영 빈도에 미치는 영향에 관해서는 아직 논란이 있다 20,22,23) . 202명 중 3명(1.5%)의 추적 단층촬영에서 새로운 병소가 발견됐고, 수술이 필요한 환자는 없었다 24) . 수술 필요성 예측에 있어서, 신경학적 악화를 확인하는 것이 일상적인 추적 단층촬영보다 정확하다 [24][25][26][27][28][29] .…”
Section: 의사의 경험unclassified
“…202명 중 3명(1.5%)의 추적 단층촬영에서 새로운 병소가 발견됐고, 수술이 필요한 환자는 없었다 24) . 수술 필요성 예측에 있어서, 신경학적 악화를 확인하는 것이 일상적인 추적 단층촬영보다 정확하다 [24][25][26][27][28][29] . 따라서 응급실 방문 당 시 또는 이후 증상이 악화한 환자가 단층촬영이 필요하다 (Fig.…”
Section: 의사의 경험unclassified
See 2 more Smart Citations